Development of a Mentalization-Based Co-Parenting Package: A Qualitative Study - Rabiee , Zahra; Yousefi , Zahra; Bahramipourisfahani , Mansoureh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to develop a mentalization-based co-parenting intervention package. The research was conducted through three consecutive studies. The objective of the first study was to identify parenting challenges and conflicts following divorce.Methods and Materials: The research population consisted of this qualitative study divorced parents, from whom 13 participants were purposively selected based on predefined inclusion and exclusion criteria; participant number was determined according to the principle of data saturation. The research instrument was a semi-structured interview. The collected data were analyzed qualitatively using thematic analysis based on the approach of Braun and Clarke (2006).Findings: Four primary challenges were identified: (1) traumatic redefinition of the family structure after divorce by both parents, (2) parental neglect and lack of trust in the other parent’s parenting competence, (3) mutual revenge-seeking behaviors, and (4) the child as the hidden victim. The second part aimed to extract co-parenting concepts grounded in mentalization theory. The research setting included all scholarly texts related to mentalization, from which six texts were selected according to inclusion and exclusion criteria. The research tool consisted of line-by-line textual analysis. Qualitative data were analyzed using the content analysis method proposed by Hsieh and Shannon (2005). Findings indicated that the principal concepts included: (1) reflective functioning, with subcomponents involving understanding one’s own and others’ psychological states; (2) mentalization outcomes, including identity formation support and enhancement of self-regulation; (3) psychopathology, encompassing impaired mentalization and weakness or absence of mentalization foundations; (4) mentalization goals, including the development of coherent self-representation and the creation of psychological security through support seeking and empathy; and (5) therapeutic strategies and techniques, including balanced brain training and skills training. During this process, two sets of themes were systematically integrated so that post-divorce parenting challenges could be reduced through the application of mentalization techniques among parents.Conclusion: Based on these findings, the developed educational package appears suitable for promoting effective co-parenting.